Comparison of time required for traditional versus virtual orthognathic surgery treatment planning. Issue 9 (September 2016) - Wrzosek, M.K.; Peacock, Z.S.; Laviv, A.; Goldwaser, B.R.; Ortiz, R.; Resnick, C.M.; Troulis, M.J.; Kaban, L.B.
Abstract: Virtual surgical planning (VSP) is a tool for predicting complex surgical movements in three dimensions and it may reduce preoperative laboratory time. A prospective study to compare the time required for standard preoperative planning versus VSP was conducted at Massachusetts General Hospital from January 2014 through January 2015. Workflow data for bimaxillary cases planned by both standard techniques and VSP were recorded in real time. Time spent was divided into three parts: (1) obtaining impressions, face-bow mounting, and model preparation; (2) occlusal analysis and modification, model surgery, and splint fabrication; (3) online VSP session. Average times were compared between standard treatment planning (sum of parts 1 and 2) and VSP (sum of parts 1 and 3). Of 41 bimaxillary cases included, 20 were simple (symmetric) and 21 were complex (asymmetry and segmental osteotomies). Average times for parts 1, 2, and 3 were 4.43, 3.01, and 0.67 h, respectively. The average time required for standard treatment planning was 7.45 h and for VSP was 5.10 h, a 31% time reduction ( P < 0.001). By eliminating all or some components of part 1, time savings may increase to as much as 91%. This study indicates that in an academic setting, VSP reduces the time required for treatment planning of bimaxillary orthognathic surgery cases.